Analisis anteseden inovasi hijau terhadap kinerja berkelanjutan pada UMKM berbasis pangan di Kediri Raya - Izzati Ardhan Firdausyi; Endah Rahayu Lestari; Wike Agustin Prima Dania (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Nowadays, environmental problems are increasing. This is largely due to production activities carried out by large and small industries, one of which is MSMEs. The increasing number of SMEs that have sprung up also increases their impact on the environment. Increasing environmental problems encourage companies to be environmentally oriented and green innovation to be the right solution for these problems. The purpose of this study was to examine the antecedent variables of green innovation (technology capability and CSR/Corporate Social Responsibility) in MSMEs and the effect of implementing green innovation on sustainable performance. Then examine the effect of environmental dynamics in moderating the relationship between green innovation and sustainable performance. The conceptual model was verified using the Partial Least Square (PLS) method. Data were obtained from 100 food-based SMEs in Kediri Raya. The results showed that the antecedent variables (technology capability and CSR/Corporate Social Responsibility) had a significant positive effect on green innovation. Furthermore, green innovation has a significant positive effect on sustainable performance. Environmental dynamics have a significant negative effect on the relationship between green innovation and sustainable performance. The results of this study offer important implications for MSMEs to be more concerned and increase green innovation to achieve sustainable performance.